2020
DOI: 10.3390/plants9030326
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Reverse-Transcription Digital PCR for Reliable Quantification of Different Pepino Mosaic Virus Genotypes

Abstract: In recent years, pepino mosaic virus (PepMV) has rapidly evolved from an emerging virus to an endemic pathogen, as it causes significant loses to tomato crops worldwide. At present, the main control strategy for prevention of PepMV disease in tomato production remains based on strict hygiene measures. To prevent damage caused by PepMV, cross-protection is used in some countries. Reliable characterisation, detection and quantification of the pathogen are vital for disease control. At present, reverse-transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…In addition, RT-ddPCR consistently reported more DENV RNA copies in samples at low concentrations compared to qRT-PCR ( Figure 4 A). The superior detection and quantification performance of RT-ddPCR over qRT-PCR with environmental and clinical samples containing low target concentrations was also reported in previous studies on rotavirus [ 13 ], pepper mild mottle virus [ 35 ], pepino mosaic virus [ 36 ], and severe acute respiratory syndrome coronavirus 2 [ 37 ]. The results from three out of eight DENV samples detected by RT-ddPCR, but not qRT-PCR, were above LLOQ making the quantification results reportable.…”
Section: Discussionsupporting
confidence: 61%
“…In addition, RT-ddPCR consistently reported more DENV RNA copies in samples at low concentrations compared to qRT-PCR ( Figure 4 A). The superior detection and quantification performance of RT-ddPCR over qRT-PCR with environmental and clinical samples containing low target concentrations was also reported in previous studies on rotavirus [ 13 ], pepper mild mottle virus [ 35 ], pepino mosaic virus [ 36 ], and severe acute respiratory syndrome coronavirus 2 [ 37 ]. The results from three out of eight DENV samples detected by RT-ddPCR, but not qRT-PCR, were above LLOQ making the quantification results reportable.…”
Section: Discussionsupporting
confidence: 61%
“…Various studies have successfully detected and identified different genotypes of PepMV in tomato crops. Using a newly developed one-step RT digital PCR, reliable quantification of different Pepino mosaic virus genotypes has been reported and found more suitable than only RT-PCR [ 82 ]. In another study, a RT-PCR was developed for the simultaneous detection and identification of three groups of Pepino mosaic virus (PepMV): European/Peruvian, Chilean 1/US1, and Chilean 2/US2 groups in routine analysis of field tomato samples [ 83 ].…”
Section: Methods For Plant Viral Diagnosticmentioning
confidence: 99%
“…Digital PCR, on the contrary, gives an absolute quantification of the molecular target as output and can, therefore, be proposed for characterization of the calibrators needed for standard curves in qPCR analyses. As suggested by other authors [ 25 ], dPCR can hypothetically be exploited for the production of calibrators.…”
Section: Discussionmentioning
confidence: 97%